Penguatan Literasi Digital melalui Pelatihan Microsoft PowerPoint di SMK Muhammadiyah - Wahyudi, Agus Budi; Sufanti, Main; Prabawa, Andi Haris; Rahmawati, Laili Etika; Pratiwi, Dini Restiyanti; Purnomo, Eko; Noviana, Sinta Tri; Febriyanti, Rifiana (Warta LPM, 2023)
Digital literacy is one of the abilities that students must have in this digitalization era. However, the facts on the ground show that digital literacy in Vocational High Schools (SMK) has not been properly realized. From the survey results, it was found that students at Muhammadiyah Kartasura Vocational School and Muhammadiyah 4 Surakarta Vocational School were less proficient in using Microsoft Powerpoint. The purpose of carrying out this service is to increase digital literacy at SMK Muhammadiyah Kartasura and SMK Muhammadiyah 4 Surakarta. The stages carried out in the service include Pre-Test, mentoring, and Post-Test. The form of community service is in the form of mentoring and training with a participatory approach. Meanwhile, the implementation of activities is divided into several stages, namely licensing, mentoring, and evaluation. The mentoring method is by direct practice regarding the features of Microsoft PowerPoint directly and providing experience to students. The results of the service show that students are proficient in digital literacy. Previously, students were not familiar with the various features of Microsoft PowerPoint. However, after this activity, students became proficient in using the features contained in Microsoft PowerPoint. This community service has reached the target as evidenced by increasing students' skills in understanding Microsoft PowerPoint, gaining experience through practices that can produce product outputs in the form of PowerPoint and increasing digital literacy for students at SMK Muhammadiyah 4 Surakarta and SMK Muhammadiyah Kartasura. Microsoft PowerPoint digital literacy skills have increased from before and after the dedication as evidenced by the increase in pre-test and post-test results. It can be concluded that this activity can improve students' digital literacy skills. This community service activity has the hope that students who already have initial skills regarding making Microsoft PowerPoint from the results of community service can continue to practice. In addition, the school can facilitate by continuing to assist in strengthening continuous digital literacy.